PROBLEMATIKA ANAK TUNANETRA DALAM PEMBELAJARAN AL-QUR’AN BRAILLE: STUDI KASUS SISWA SLB-A NEGERI 3 MARTAPURA - Alifia Nur Rizkilah; Liya Azizah; Nor hidayah; Najib Irsyadi (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Abstract This study explores the challenges faced by blind students in learning the Qur'an using Braille at SLB-A Negeri 3 Martapura. The background highlights the importance of inclusive education and the right to religious learning for students with visual impairments. The aim is to identify both internal and external problems experienced by these students and to describe effective strategies applied by teachers and schools to overcome them. Using a qualitative case study approach, the data were collected through observation, interviews, and documentation involving teachers and students. The findings reveal that internal problems include low self-confidence, difficulty recognizing Braille Qur'anic letters, limited concentration, and lack of motivation. Meanwhile, external problems involve the shortage of competent Qur'an Braille teachers, though this is mitigated by adequate facilities and supportive environments. The school adopts several strategies, such as the multisensory Abahata method, the use of Braille learning tools, individual mentoring, motivation reinforcement, and participation in Qur'anic competitions to build confidence and skills. The conclusion emphasizes that the challenges of learning Qur'an Braille among blind students are not insurmountable but require consistent support, adaptive teaching methods, and a collaborative environment. This study underscores the significance of holistic and empathetic educational approaches in empowering visually impaired students in religious literacy. Keywords: Visually Impaired, Qur'an Braille, Inclusive Learning, Learning Challenges, Teaching Strategies.